Археологічні дослідження Цареборисівської фортеці у 2009 р. - Голубєва, І.В. (Археологічні дослідження в Україні, 2010)
Brief information on results of the research of the Fortress of Tsar Borys in 2009 is given. Study of dytynets (citadel) of the fortress was continued. As a result of archaeological prospecting in suburbs of the hill-fort one more posad (trading quarter) is recorded and a small prospecting trench is laid on it. Representative series of artifacts is obtained.